1997
DOI: 10.1093/ptj/77.10.1090
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Time and Frequency of Static Stretching on Flexibility of the Hamstring Muscles

Abstract: The results of this study suggest that a 30-second duration is an effective amount of time to sustain a hamstring muscle stretch in order to increase ROM. No increase in flexibility occurred when the duration of stretching was increased from 30 to 60 seconds or when the frequency of stretching was increased from one to three times per day.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
248
5
81

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 457 publications
(355 citation statements)
references
References 8 publications
12
248
5
81
Order By: Relevance
“…In the literature, the frequency for undertaking stretching exercises in different diseases and among older patients has varied from 2 to 7 days/week [2,25]. We provided a daily recommendation to ensure the best effect to increase flexibility, with sufficient stretching time [3,4,29] and frequency [3,13]. The recommended minimum frequency for muscle strengthening exercises was 3-5 days/week.…”
Section: The Interventionmentioning
confidence: 99%
“…In the literature, the frequency for undertaking stretching exercises in different diseases and among older patients has varied from 2 to 7 days/week [2,25]. We provided a daily recommendation to ensure the best effect to increase flexibility, with sufficient stretching time [3,4,29] and frequency [3,13]. The recommended minimum frequency for muscle strengthening exercises was 3-5 days/week.…”
Section: The Interventionmentioning
confidence: 99%
“…Não há aumento de fl exibilidade quando a duração do alongamento é aumentada de 30 a 60 segundos, ou quando a frequência de alongamento é aumentada de uma a três vezes por dia (18,23). Corroborando com outros estudos (13,14,18,22,23), optou-se pela realização de apenas uma única sessão de alongamento estático e sua sustentação por um período de 60 segundos, sendo observada sua efi cácia nos alongamentos.…”
Section: Discussionunclassified
“…O alongamento pode variar quanto à técnica, tais como alongamento balístico, estático (sustentado), FNP (Facilitação Neuromuscular Proprioceptiva), entre outros; e quanto ao posicionamento do indivíduo (sentado, ortostase, decúbitos) (11,18,19).…”
unclassified
See 1 more Smart Citation
“…One study demonstrated that there is equal effectiveness for stretching once a day when compared to stretching 3 times a day and that holding a stretch for 30 seconds is as effective holding 1 for 60 seconds (12). It has also been revealed that stretching muscles of the lower extremity had a resulting increase in flexibility for 90 minutes (13).…”
Section: Literature Regarding Stretchingmentioning
confidence: 99%